CyTOF profiling identifies location-specific peripheral immune checkpoint and immune cell subset in mild ischemic stroke - Hang, Hang; Yao, Yang; Wang, Likun; Liu, Cuiying; Zhao, Jing; Xu, Baohui; Zhao, Heng; Wu, Guofeng (Frontiers in Immunology, 2026)
IntroductionMild ischemic stroke accounts for over half of all stroke cases, yet how peripheral immune responses evolve over time—and how they differ by infarct location—remains poorly defined.MethodsPeripheral blood was collected from ten patients with mild ischemic stroke and five matched controls at days 1, 3, and 7 after onset. Patients were stratified by cortical or subcortical infarction. High-dimensional mass cytometry was used to characterize immune cell composition and immune checkpoint expression.ResultsSubcortical infarction was associated with sustained expansion of classical monocytes, persistent reduction of intermediate monocytes, and delayed PD-1/PD-L1 regulatory signaling, indicating prolonged myeloid-driven inflammation. In contrast, cortical infarction exhibited a more balanced monocyte profile and earlier PD-1 upregulation on dendritic cells and classical monocytes. CD4⁺ and CD8⁺ T-cell subsets showed distinct, location-dependent dynamics: cortical infarction induced earlier modulation of memory and regulatory phenotypes, whereas subcortical infarction produced slower but more persistent shifts. CCR5-defined CD8⁺ T-cell subsets also differed markedly, with subcortical infarction showing enrichment of CCR5⁺ effector cells, reduced checkpoint expression, and contraction of the CCR5⁻ compartment.DiscussionPeripheral immune remodeling in mild ischemic stroke displays clear infarct location–specific trajectories. These findings highlight infarct topology as a critical determinant of post-stroke immune regulation and support the development of location-adapted immunomodulatory strategies.